Discourse, Evidentiality and the Seventh Son Healing Tradition in French-Newfoundland Culture - Butler, Gary (Ethnologies, 1994)
This article deals with the symbolic construction through discourse of the belief matrix surrounding the seventh son healing tradition in French-Newfoundland culture. It discusses the discourse strategies which serve not only to disseminate the knowledge of this tradition, but also to support the belief in its legitimacy. An historical overview of this tradition in France and North America is also provided.